PEDAGOGICAL MECHANISMS OF ENSURING EFFECTIVENESS OF ENGLISH LANGUAGE TEACHING IN TRAINING FUTURE DEFECTOLOGISTS - (PhD) Aliyeva Dilafruz (Galaxy International Interdisciplinary Research Journal, 2023)
The article shows that teacher’s high level of communicative competence determined to fully use his language knowledge, as well as communicative abilities and skills in working with students, unlikely to be able to teach English communication. Also, a positive relationship between motivational orientations and student achievement.